Corporate taxes, productivity, and business dynamism - Andrea Colciago; Vivien Lewis; Branka Matyska (Deutsche Bundesbank, 2023)
We identify the effects of corporate income tax shocks on key US macroeconomic aggregates. In response to a corporate income tax cut, we find that: (i) labor productivity increases; (ii) entry increases with delay; (iii) exit increases; (iv) total labor increases by more than production labor. To rationalize these empirical findings, we build a New Keynesian model with idiosyncratic firm productivity, and entry and exit. Our model features productivity gains due to selection and cleansing along the entry and exit margins. Models with homogeneous firms fail to account for the selection and cleansing process and produce counterfactual results.
Keywords: E62; E32; H25; 330; corporate taxation; productivity; firm entry and exit